Análisis económico-financiero de las empresas concesionarias de automóviles en Espa\~na - Paz Rico Belda (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2015)
– This paper makes an economic and financial analysis of car dealerships in Spain, using data from SABI database. Moreover, it analyses the economic and financial characteristics of firms that determinate that, in the same crisis context, some firms manage to have positive profit, while other ones have losses. For doing that, a binary choice model is estimated, which allows to conclude that companies with best behavior against the crisis have been the largest, who have reduced its debt while increasing its liquidity ratio and its capacity to return its debt. The youngest firms are better adapted to the crisis and finally has also positively influenced if firms have been able to contain costs.
Keywords: L62; D21; 330; car dealerships; profitability; financial statements; leverage